2020
DOI: 10.1007/s11661-020-06022-6
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Ms Temperature as a Function of Composition and Grain Size

Abstract: Martensite transformation was studied in 16 steel compositions with various C, Mn, Si, Al, and Cr contents. Different annealing treatments were performed on the elaborated steels to obtain different prior austenite grain sizes (PAGSs) and M s temperatures. This permitted the concomitant evolution of M s temperature as a function of chemical composition and PAGS. The experimentally built database allowed the decorrelation of the effects of chemical composition and PAGS, and a new empirical equation to predict M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…The martensite start temperature, Ms, was measured at all selected T conditions, and when possible, the prior austenite grain size (PAGS) was revealed and measured as well; the results thus obtained are presented in Figure 2. It is clear that the effect of the austenitisation heat treatment and thus, of the PAGS on the Ms of the steels, is very limited if not negligible, which agrees with recent reports that show that average austenite grain sizes above 15-20 µm have a negligible effect on the Ms temperature of steels [25][26][27].…”
Section: Austenitisation Conditionssupporting
confidence: 90%
“…The martensite start temperature, Ms, was measured at all selected T conditions, and when possible, the prior austenite grain size (PAGS) was revealed and measured as well; the results thus obtained are presented in Figure 2. It is clear that the effect of the austenitisation heat treatment and thus, of the PAGS on the Ms of the steels, is very limited if not negligible, which agrees with recent reports that show that average austenite grain sizes above 15-20 µm have a negligible effect on the Ms temperature of steels [25][26][27].…”
Section: Austenitisation Conditionssupporting
confidence: 90%
“…15(b) and 13, it was implied that the decrease in the average intercept length of the prior austenite grains from 2 to 1 μm stabilized the austenite, which corresponded to a reduction of 110°C in the apparent Ms temperature. However, the reduction in the Ms temperature was estimated to be approximately 30°C when extrapolating the decrease in the average intercept length from 2 to 1 μm in the model, 31) which is validated in the prior austenite grain diameter range greater than 6 μm. Therefore, it is suggested that the calculated ∆Ms incorporated the effects other than that of the prior austenite grain size, such as the density of the low-angle subgrain boundaries, 15) which increases concurrently with grain refinement.…”
Section: Effect Of Austenite Grain Size On Austenite Stability In Sti...mentioning
confidence: 66%
“…To define the Tq, the method described in [4] was used but the formulas and criteria were modified as follows. Ms value was estimated using the formula reported in [9] and assuming the PAGS to be around 15µm:…”
Section: Methodsmentioning
confidence: 99%